Prevalence, Clinical Presentation, and Prognostic Implications of Orbital Complications in Rhinosinusitis Patients with Systemic Comorbidities - Ayesha Ghafoor, Hafiz Syed Umar Abdur Rehman, Anwar. Ul. Haq, Allah Bux Mushtaq, Wing Commander Muhammad Tahir Shah, Aimal Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Orbital complications of rhinosinusitis represent serious, potentially vision-threatening conditions that are often worsened by underlying systemic comorbidities such as diabetes mellitus, hypertension, and immunosuppression. These comorbidities alter immune function, promote infection spread, and increase the risk of complications, but data on their specific impact remain limited in regional populations. Objective: To determine the prevalence, clinical presentation, and prognostic implications of orbital complications in rhinosinusitis patients with systemic comorbidities. Methods: A cross-sectional study was conducted from February 2022 to March 2023 at THQ Hospital Depalpur and Syed Eye Care, Syed Medical Centre, Bahawalpur. A total of 80 patients aged ≥12 years with clinically and radiologically confirmed orbital complications secondary to rhinosinusitis were enrolled. Detailed clinical history, systemic comorbidities, imaging findings, and treatment outcomes were documented and analyzed using SPSS version 26. Results: Out of 80 patients, 56 (70%) had at least one systemic comorbidity, with diabetes mellitus being the most common (43.8%), followed by hypertension (32.5%). Orbital cellulitis (40%) was the most frequent complication, followed by subperiosteal abscess (22.5%) and orbital abscess (13.8%). Patients with comorbidities had significantly more severe presentations, including proptosis (60.7% vs. 20.8%), ophthalmoplegia (50% vs. 16.7%), and visual impairment (41.1% vs. 12.5%) compared to non-comorbid patients. They also had longer hospital stays (8.9 ± 2.6 vs. 5.3 ± 1.9 days, p<0.001), higher rates of surgical intervention (51.8% vs. 29.1%, p=0.028), and worse visual outcomes, including all cases of permanent vision loss. Conclusion: Systemic comorbidities significantly increase the severity and worsen the prognosis of orbital complications in rhinosinusitis. Diabetic and hypertensive patients are especially vulnerable to advanced orbital disease, delayed recovery, and visual loss. Early diagnosis, aggressive multidisciplinary management, and risk stratification in comorbid patients are essential to reduce complications and improve outcomes. Keywords: Rhinosinusitis, Orbital complications, Diabetes mellitus, Systemic comorbidities, Orbital cellulitis, Visual prognosis